The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1002/jmri.28854
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Assessment of Myocardial Edema by MR T2 Mapping in Children With Kawasaki Disease

Lei Hu,
Shi‐gan‐mo A‐zhe,
Zhong‐qin Zhou
et al.

Abstract: BackgroundFew studies assessed myocardial inflammation using Cardiovascular Magnetic Resonance Imaging in Kawasaki disease (KD) patients.PurposeTo quantify myocardial edema in KD patients using T2 mapping and explore the independent predictors of T2 values.Study TypeProspective.SubjectsNinety KD patients including 40 in acute phase (26 males, 65.0%) and 50 in chronic phase (34 males, 68.0%). Thirty‐one healthy volunteers (21 males, 70.0%).Field Strength/Sequence3.0 T T2‐weighted Turbo Spin Echo‐Short Time of I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…6 In the present study, the authors prospectively quantified myocardial edema by comparing 31 controls and 90 patients with KD (including 40 with acute-phase and 50 with chronic-phase) using cardiac MRI and explored the independent predictors of T2 values. 7 To our knowledge, this is the first study to quantitatively evaluate myocardial edema in KD patients with T2 mapping. The authors concluded that global and regional myocardial edema were present in patients with KD and were more pronounced in patients with acute KD than in those with chronic KD.…”
mentioning
confidence: 92%
“…6 In the present study, the authors prospectively quantified myocardial edema by comparing 31 controls and 90 patients with KD (including 40 with acute-phase and 50 with chronic-phase) using cardiac MRI and explored the independent predictors of T2 values. 7 To our knowledge, this is the first study to quantitatively evaluate myocardial edema in KD patients with T2 mapping. The authors concluded that global and regional myocardial edema were present in patients with KD and were more pronounced in patients with acute KD than in those with chronic KD.…”
mentioning
confidence: 92%